The Natural Products Targeting on Allergic Rhinitis: From Traditional Medicine to Modern Drug Discovery - Suhyun Lim; Iwah Jeong; Jonghyeok Cho; Chaewon Shin; Kwan-Il Kim; Bum-Sang Shim; Seong-Gyu Ko; Bonglee Kim (Antioxidants, 2021)
More than 500 million people suffer from allergic rhinitis (AR) in the world. Current treatments include oral antihistamines and intranasal corticosteroids; however, they often cause side effects and are unsuitable for long-term exposure. Natural products could work as a feasible alternative, and this study aimed to review the efficacies and mechanisms of natural substances in AR therapies by examining previous literature. Fifty-seven studies were collected and classified into plants, fungi, and minerals decoction; clinical trials were organized separately. The majority of the natural products showed their efficacies by two mechanisms: anti-inflammation regulating diverse mediators and anti-oxidation controlling the activity of nuclear factor kappa-light-chain-enhancer of activated B cells (NFκB) pathway stimulated by reactive oxygen species (ROS). The main AR factors modified by natural products included interleukin (IL)-4, IL-5, IL-13, interferon-gamma (IFN-γ), tumor necrosis factor-α (TNF-α), cyclooxygenase 2 (COX-2), and phospho-ERK1/2 (p-ERK1/2). Although further studies are required to verify their efficacies and safeties, natural products can significantly contribute to the treatment of AR.